Comment on: 'Solving the conformable Huxley equation using the complex method' [Electron. Res. Arch., 31 (2023), 1303–1322] - Feng Ye; Xiaoting Zhang; Chunling Jiang; Bo Zeng (Electronic Research Archive)
Using the complex method, Guoqiang Dang and Qiyou Liu [Guoqiang Dang, Qiyou Liu, Electron. Res. Arch., 31 (2023), 1303–1322] have found some exact solutions of the conformable Huxley equation. In this comment, we first demonstrate that the elliptic function solutions and rational function solutions do not satisfy the complex conformable Huxley equation. Finally, all exact solutions of the conformable Huxley equation are given by us.